Demystifying the relevance of size amongst macro- and micro-corticotropinoma: Experience in 206 patients - Rahul Gupta; Nimisha Jain; Anil Bhansali; Sanjay K Bhadada; Rama Walia (Indian Journal of Endocrinology and Metabolism, 2022)
Objective: In individuals with adrenocorticotrophic hormone (ACTH)-dependent Cushing's syndrome (CS), to estimate the differences between micro-corticotropinoma (size ≤6 mm and 6-10 mm), macro-corticotropinoma (>10 mm) and ectopic Cushing's syndrome (ECS), in relation to their epidemiological, clinical and biochemical parameters. Methods: In individuals with CS, the clinical and hormonal parameters, and magnetic resonance imaging of sella were collected from 1984 to 2019. A total of 138 cases of micro-corticotropinoma, 47 cases of macro-corticotropinoma and 21 cases of ECS were compared. Results: Except for size, there were no differences in biochemical and hormonal parameters of macro- and micro-corticotropinoma, irrespective of their size (≤6 mm, 6-10 mm and >10 mm). In comparison to Cushing's disease (CD), individuals with ECS had a male predominance (F:M ratio of 2.4:1 vs. 0.5:1), shorter duration from onset of symptoms to diagnosis (24 vs. 12 months). They also had a higher ACTH (139 vs. 65.8 pg/ml), 0800h cortisol (1200 vs. 880 nmol/l), 2300h cortisol (1100 vs. 700 nmol/l) and cortisol levels after high dose dexamethasone suppression test (1050 vs. 244.5 nmol/l). Conclusion: The biochemical phenotype of macro-corticotropinoma resembles that of micro-corticotropinoma despite their larger tumour size, suggesting that the former is relatively less functional. Micro-corticotropinoma ≤6 mm and 6-10 mm have a similar clinical and biochemical profile. As compare to CD, ECS is characterised by a higher disease burden as reflected in their higher cortisol, more autonomicity and loss of rhythmicity.